Marketing of Maize in Gobichettipalayam Taluk - S. Rajeshkanna, S. Rajeshkanna; S. Arulraj, S. Arulraj (Journal of Neonatal Surgery, 2025)
This study evaluated the marketing of maize in Gobichettipalayam Taluk, focusing on the current marketing channels, factors influencing the choice of these channels, and the challenges faced by maize farmers. The research utilizes a combination of primary data collection through surveys and interviews with maize farmers, wholesalers, and retailers, along with secondary data from local agricultural reports. The findings reveal that local markets, middlemen, and cooperatives play a dominant role in maize marketing, but farmers face significant challenges including price fluctuations, poor infrastructure, and limited access to larger retail markets. Factors such as price, transportation costs, and market knowledge heavily influence the choice of marketing channels. The study concludes by recommending the adoption of digital platforms, better coordination between farmers and buyers, and improved infrastructure to enhance the efficiency and profitability of maize marketing. These strategies could alleviate the existing challenges and optimize maize sales in the region.